The subjective experience of personhood in dementia care settings. (July 2013) - Nowell, Zoe C; Thornton, Amanda; Simpson, Jane
Within the social psychological understanding of dementia, individuals' personhood is central. A respect for personhood has been linked to successful person-centred care, yet research exploring subjective personhood in dementia is scarce. This study aimed to understand personhood by exploring the subjective experiences of those with dementia. Seven individuals with dementia were interviewed and interpretative phenomenological analysis was used to identify themes across accounts. Themes identified were: (1) working out the system and adapting in order to survive it – the 'peoplehood' of the system; (2) using past and future roles and experiences to manage the present – the transient nature of personhood; (3) being both an individual and a member of a group − the conflict of a dual role. The themes highlighted showed that individuals with dementia supported their personhood by drawing on their own, others' and the system's resources. The findings are discussed and links with existing literature and clinical implications are considered.